The Role of Correctional Officers in Enhancing Legal Awareness Among Inmates at Class IIB Pacitan State Detention Center - Mudumi, Erdi Christian Priyanto; Rohayati , Ade Cici (Universitas Dehasen Bengkulu, 2025)
Indonesia, as a country with diverse ethnic groups, faces significant challenges in maintaining pluralism and tolerance, especially in the context of conflicts that are vulnerable among the tribes. This research aims to analyze the role of correctional officers in enhancing the legal awareness of inmates at the Class IIB State Detention Center in Pacitan. Using a qualitative approach, data was collected through in-depth interviews, observations, and document studies. The results show that correctional officers play an important role in providing legal understanding, fulfilling the rights of inmates, and acting as good role models. However, obstacles such as limited human resources and the discipline of personnel hinder the effectiveness of coaching. The legal awareness of inmates has increased through the outreach and guidance programs implemented, but there is a need for evaluation and enhancement of the staff's competencies to achieve optimal results. This research emphasizes the important role of officers in creating an environment that supports legal awareness among inmates, which in turn contributes to order and justice in society.